Cognitive impairments after surgical repair of ruptured and unruptured aneurysms. Issue 5 (1st November 2000) - Hillis, Argye E; Anderson, Nancy; Sampath, Prakesh; Rigamonti, Daniele
Abstract : OBJECTIVES: To determine the frequency and severity of neuropsychological impairments associated with aneurysmal subarachnoid haemorrhage, and associated with repair of intracerebral aneurysms. METHODS: Two groups of patients who underwent repair of intracerebral aneurysms were studied: patients with unruptured aneurysms (n=20) and patients with ruptured aneurysms (n=27). All patients were administered a battery of standardised neuropsychological tests about 3 months after surgery. A subset of 12 patients with unruptured aneurysms were administered the battery both before and after elective repair of the aneurysm(s). A subset of six patients with ruptured aneurysms were given the test at both 3 months and 1 year after surgery. RESULTS: As previously reported for patients with ruptured aneurysms, patients with both ruptured and unruptured aneurysms performed, as a group, significantly below published norms on many of the neuropsychological tests after surgery. However, there were significant differences between preoperative and postoperative performance in the unruptured aneurysm group only on a few tests: measures of word fluency, verbal recall, and frontal lobe function. Performance of patients with ruptured aneurysms was significantly below that of patients with unruptured aneurysms only on a few tests of verbal and visual memory. In addition, group differences compared with published norms reflected severely impaired performance by a minority of patients, rather than moderately impaired performance in a majority of patients. CONCLUSIONS: Although patients who undergo repair of ruptured aneursyms perform, as a group, below published norms on many neuropsychological tests, significant impairments are seen in a minority of patients. Some of the impairments are associated with subarachnoid haemorrhage, whereas others (found in patients who underwent repair of unruptured aneurysms) are due to general effects of neurosurgery and perioperative management. Finally, some of the postoperative deficits are merely a reflection of premorbid weaknesses.